2014
DOI: 10.3109/02770903.2014.903964
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of Brazilian adolescents with asthma: associated clinical and sociodemographic factors

Abstract: The level of asthma control was related to QOL, but this association manifested mainly in the subjective control domains, such as nighttime and daytime symptoms and physical activity limitations. The objective domain for control classification, represented by pulmonary function, was not an independent predictor or determinant of the QOL of adolescent asthma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
(32 reference statements)
1
22
1
Order By: Relevance
“…The most frequently used generic QoL instruments were the Pediatric Quality of Life Inventory (PedsQL) or an adapted version of the PedsQL (six studies), 12,15,20,21,35,36 the Short-form 36 (SF-36; two studies), 14,34 the Impact of Childhood Illness scale (two studies), 25,28 the Child Health Questionnaire-Parent Form (one study), 26 the DISAB-KIDS chronic generic model (one study) 31 and the KINDL questionnaire (one study). 27 Disease-specific questionnaires included the Paediatric Asthma Quality of Life Questionnaire (six studies), [6][7][8][9][10][11] the Quality of Life in Children with Epilepsy (QOLCE) questionnaire (five studies), 16,17,24,26,29 the Quality of Life in Epilepsy Inventory for Adolescents (QOLIE-AD-48; three studies), 18,19,27 the PedsQL T1DM module (two studies), 32,33 the Diabetes Quality of Life for Youth short form (one study), 30 the Impact of Epilepsy Schedule (one study) 22 and the Epilepsy and Children questionnaire (one study). 23 Single-domain SES factors included household income (11 studies), [6][7][8]11,[14][15][16]22,26,29,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently used generic QoL instruments were the Pediatric Quality of Life Inventory (PedsQL) or an adapted version of the PedsQL (six studies), 12,15,20,21,35,36 the Short-form 36 (SF-36; two studies), 14,34 the Impact of Childhood Illness scale (two studies), 25,28 the Child Health Questionnaire-Parent Form (one study), 26 the DISAB-KIDS chronic generic model (one study) 31 and the KINDL questionnaire (one study). 27 Disease-specific questionnaires included the Paediatric Asthma Quality of Life Questionnaire (six studies), [6][7][8][9][10][11] the Quality of Life in Children with Epilepsy (QOLCE) questionnaire (five studies), 16,17,24,26,29 the Quality of Life in Epilepsy Inventory for Adolescents (QOLIE-AD-48; three studies), 18,19,27 the PedsQL T1DM module (two studies), 32,33 the Diabetes Quality of Life for Youth short form (one study), 30 the Impact of Epilepsy Schedule (one study) 22 and the Epilepsy and Children questionnaire (one study). 23 Single-domain SES factors included household income (11 studies), [6][7][8]11,[14][15][16]22,26,29,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…27 Disease-specific questionnaires included the Paediatric Asthma Quality of Life Questionnaire (six studies), [6][7][8][9][10][11] the Quality of Life in Children with Epilepsy (QOLCE) questionnaire (five studies), 16,17,24,26,29 the Quality of Life in Epilepsy Inventory for Adolescents (QOLIE-AD-48; three studies), 18,19,27 the PedsQL T1DM module (two studies), 32,33 the Diabetes Quality of Life for Youth short form (one study), 30 the Impact of Epilepsy Schedule (one study) 22 and the Epilepsy and Children questionnaire (one study). 23 Single-domain SES factors included household income (11 studies), [6][7][8]11,[14][15][16]22,26,29,30 mother's education (15 studies), 6,[9][10][11][12]16,17,21,22,24,25,29,31,34,36 father's education (11 studies),…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorly controlled asthma can be very disruptive to the daily life activities for the child through increased school absences, impaired sleep, and restricted social and physical activity (Dean et al, 2010; Wildhaber, Carroll & Brand, 2012), resulting in lower child quality of life (Amaral, Moratelli, Palma, & Leite, 2014). The burden of asthma exacerbations likewise reverberates throughout families who describe substantial psychosocial, caregiving, and financial stresses (Crespo, Carona, Silva, Canavarro, & Dattilio, 2011; Sampson et al, 2013a; Sampson et al, 2013b), beyond the fear of seeing their child struggling to breathe.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, a search of adolescents with asthma, found that of 114 adolescents interviewed, most had less than 15 years old and were male gender [11]. It can be observed that the results of a survey conducted in Australia, came to corroborate the data of the Brazilian study and shows that asthma has a higher incidence in males than in females.…”
Section: Relations Between Demographic Variables (Race Color and Sexmentioning
confidence: 77%